A systemic transformation of an arts and sciences curriculum to nurture inclusive excellence of all students through course-based research experiences - Delogu, Franco; Nelson, Michelle; Timmons, Shannon C.; Weinstein, Melinda; Bhattacharya, Bhubanjyoti; Jaussen, Paul; Al-Hamando, Mazin; Al-Azary, Hamad; Anyaiwe, Oriehi; Appleby, LaVetta; Bukaita, Wisam; Cartwright, Christopher; et al. (Frontiers in Education, 2023)
We describe herein a large-scale, multidisciplinary course-based undergraduate research experience program (CRE) developed at Lawrence Technological University (LTU). In our program, all students enrolled in CRE classes participate in authentic research experiences within the framework of the curriculum, eliminating self-selection processes and other barriers to traditional extracurricular research experiences. Since 2014, we have designed and implemented more than 40 CRE courses in our College of Arts and Sciences involving more than 30 instructors from computer science, mathematics, physics, biology, chemistry, English composition, literature, philosophy, media communication, nursing, and psychology. Assessment survey data indicates that students who participate in CRE courses have an enhanced attitude towards research and discovery, as well as increased self-efficacy. This intervention is particularly relevant for non-traditional students, such as students who commute and/or have significant work or childcare commitments, who often experience limited access to research activities. Herein we highlight the importance of a systemic institutional change that has made this intervention sustainable and likely to outlast the external funding phase. Systemic change can emerge from a combination of conditions, including: 1. Developing a critical mass of CRE courses by providing instructors with both incentives and training; 2. Developing general principles on which instructors can base their CRE activities; 3. Securing and maintaining institutional support to promote policy changes towards a more inclusive institution; and 4. Diversifying the range of the intervention, both in terms of initiatives and disciplines involved.